Manipulation of frozen water droplets with nano-particles - Hilman Abdul Halim (2019)
Nanofluids are engineered colloids consisting of conventional heat transfer fluids and nanoparticles that have enhanced thermal properties. One of these nanoparticles is TiO2 and it is frequently used due to its high stability in terms of chemical structure and physical properties. An interesting phenomenon was observed when a droplet of TiO2 nanofluid was subjected to freezing: a flat top was formed at the tip of the droplet. In order to understand more regarding this phenomenon, the experiment used six varying concentrations of TiO2 and two solid substrates of different wettability as variables in the dropwise freezing of a nanofluid droplet. The results were quantified by a dimensionless height/width ratio, and subsequently analysed with respect to the amount of concentration used, alongside the duration of freezing time. Based on the results, it was found that higher levels of concentration of TiO2 gives a higher height/width ratio, but no model could be formed to properly establish this relationship. Higher concentration of TiO2 nanofluid also extends the freezing duration by retarding ice nucleation, though no clear relationship could be established from the results. Areas for future research were also proposed mainly in how the heat transfer affects the freezing front and wettability of the substrate could affect the geometry of the frozen TiO2 nanofluid droplet.